PEMBERIAN LANCAU WOLIO TERHADAP PENURUNAN TEKANAN DARAH LANSIA - Sitti Aisyah Ansi; Wa Ode Nesya Jeni , Samrida (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The Comparative Study of the Lancau Wolio Giving to Lowering Blood Pressure of Elderly Hypertension in Katobengke Public Health Center working area in 2020. The purpose of this study was to determine the effectiveness of Lancau Wolio potion in lowering blood pressure of elderly hypertension compared to other medication. The research was a quantitative approach and a quasi-experimental that compares the results of the intervention group and the control group. The intervention group comsume the Lancau Wolio and the control group taking medical drugs (Captopril) in lowering blood pressure. The results of this study showed a decrease of systolic blood pressure on the intervention group after consuming Lancau Wolio for two weeks (p = 0.003) and there was no difference in diastolic blood pressure on the intervention group before and after treatment (p = 0.255).In this study, Lancau Wolio was proven to be an alternative medication for hypertension which is effective in reducing systolic blood pressure by 9.32% on intervention group of elderly in Katobengke Public Center working area..